Fertility cost, intergenerational labor division, and female employment - Haiyue Yu; Jin Cao; Shulong Kang (Bank of Finland, Institute for Economies in Transition (BOFIT), 2019)
This paper considers the role of grandparental childcare in China's extraordinarily high female labor-market participation rate. Indeed, the high female labor-market participation and low labor-income penalty for childbirth is all the more remarkable given the lack of public subsidies for childcare. Using a novel and high-quality dataset, we find that childcare provided by retired grandparents significantly reduces the duration of career breaks for young women and helps women remain in the labor force. We further show that well-educated urban women benefit most from grandparental childcare, especially in the first three years of the child's life before there is a possibility to enter kindergarten.
URN:NBN:fi:bof-201907291310
Keywords: C24; J13; J22; 330; intergenerational labor division; grandparental childcare; female employment; human capital accumulation